Peningkatan Pengetahuan Ibu Mengenai Gizi Seimbang Dalam Pemenuhan Gizi Keluarga - Rifatul Masrikhiyah (Universitas Lancang Kuning, 2020)
The prevelency of children's nutritional problems is still high, not only the lack of nutritional problems resulting in children stunting and uderweight; And more nutrients that cause obesity and diabetes. One of the causes of nutritional problems is ignorance about healthy menu and lack of awareness of Kadarzi. This activity aims to improve the knowledge of mothers on balanced nutrition in the fulfillment of family nutrition. PkM is held in Sengon village RT/RW 001/003 kedependants District Brebes in July 2019. The subjects that followed the activities amounted to 25 mothers – housewives. This activity consists of 3 stages including: preparation stage, implementation stage and interview stage. Data is obtained from pre test results and post tests and discussions. Results of this activity is an increase in the knowledge of the mother about balanced nutrition in the fulfillment of family nutrition, there is an increase from 12% to 76%